Generation Specific Patterns of Communication based on the Supply Chain management in the Digital Society - Vladimir A.Koshel; Tatiana L.Shklyar; Svetlana A.Avtonomova; Marina G.Shilina (International Journal of Supply Chain Management, 2019)
The overwhelming digitalization of society has affected all the spheres of an individual’s life, be it one’s worldview, the mechanisms of thinking, the ways of dealing with information, and, obviously, the patterns of communication. The changes of the field of communications are manifest in the style and the symbolism of language as well as its effects on supply chain strategy.Both Russian and foreign experts point at a difference between generations when it comes to communication. Similarly, researchers contend that this difference owes to information and communication technologies.The authors of this article set a goal to find out generation specific features of communication and focus on how these features show in different areas of life. The awareness of the different ways of perceiving messages by different segments of the target audience will enable professionals in the field of communications to draft those messages in the most appropriate way and be most efficient when addressing the respective target audience. This article presents the results of a study and an analysis conducted by the authors, which aims at finding out the differences in the area of communications shown by generations X, Y and Z. Based on the results of the research and the analysis mentioned above, the authors offer specific recommendations for each one of the target audience segments considered.